2021
DOI: 10.1002/jbm4.10507
|View full text |Cite
|
Sign up to set email alerts
|

Refracture and mortality following hospitalization for severe osteoporotic fractures: The Fractos Study

Abstract: Severe osteoporotic fractures (hip, proximal humerus, pelvic, vertebral and multiple rib fractures) carry an increased risk of mortality. This retrospective cohort study in the French national healthcare database aimed to estimate refracture and mortality rates after severe osteoporotic fractures at different sites, and to identify mortality‐related variables. A total of 356,895 patients hospitalized for severe osteoporotic fracture between 2009 and 2014 inclusive were analyzed. The cohort was followed for 2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 57 publications
3
35
4
1
Order By: Relevance
“…The findings of this investigation with an approximately 15% increase of fragility fracture occurrence per decade of life in both sexes confirm the magnitude of the population burden in this country. Except for rib fractures, women were affected substantially more frequently, especially at locations such as the forearm (1:6 ratio) and the pelvis (1:5 ratio), which is in line with recently reported data from France [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of this investigation with an approximately 15% increase of fragility fracture occurrence per decade of life in both sexes confirm the magnitude of the population burden in this country. Except for rib fractures, women were affected substantially more frequently, especially at locations such as the forearm (1:6 ratio) and the pelvis (1:5 ratio), which is in line with recently reported data from France [26].…”
Section: Discussionsupporting
confidence: 91%
“…In a study from France, only 16.7% received a specific osteoporosis treatment in the 12 months after a fracture. The refracture rate within the first year after fracture was 6.3%, with lower rates for multiple rib fractures (4.0%) and higher rates for pelvic fractures (7.8%) [26]. A recent study of the impact of antiosteoporotic drugs and calcium/ vitamin D on refracture in patients with previous fragility fractures showed that over a mean follow-up of 3 years, the risk of subsequent fractures was 44.4% lower in treated patients compared to untreated ones and 77.2% lower in treated patients who were adherent to medication [38].…”
Section: Discussionmentioning
confidence: 91%
“…Cortical bone comprises about 80% of the total bone mass and this bone compartment is important for skeletal strength, not only in long bones, but also in vertebrae (Roux et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, contralateral osteoporotic hip fractures are reported approximately 8.54% (range 5-10%) [ 19 - 21 ]. Roux et al [ 22 ], in the Fractos study (from the French national healthcare database), evaluated 356,895 patients hospitalized for severe osteoporotic fracture; in the 12 month-period following fracture, only 58,220 patients (16.7%) received a specific osteoporosis treatment, of whom 21,228 were previously treatment‐naïve. The 12‐month refracture rate and the all-cause mortality after the hip fracture have been estimated at 7.8% and 12.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%